Extended loci histocompatibility matching in HSCT—Going beyond classical HLA. (9th June 2021) - Neuchel, Christine; Fürst, Daniel; Tsamadou, Chrysanthi; Schrezenmeier, Hubert; Mytilineos, Joannis
Abstract: Unrelated haematopoietic stem cell transplantation (HSCT) has evolved from an experimental protocol to a potentially curative first‐line treatment in a variety of haematologic malignancies. The continuous refinement of treatment protocols and supportive care paired with ongoing achievements in the technological field of histocompatibility testing enabled this transformation. Without a doubt, HLA matching is still the foremost criterion for donor selection in unrelated HSCT. However, HSCT‐related treatment complications still occur frequently, often resulting in patients suffering severely or even dying as a consequence of such complications. Current literature indicates that other immune system modulating factors may play a role in the setting of HSCT. In this review, we discuss the current clinical evidence of a possible influence of nonclassical HLA antigens HLA‐E, HLA‐F, and HLA‐G as well as the HLA‐like molecules MICA and MICB, in HSCT.